Possibilities Of Increasing Motivation Of Girls Wrestlers With The Help Of Physical Exercises - pcadminАхмадалиева Максуда (Genius Journals, 2025)
The article confirms the need to develop scientifically based physical education programs for students, which help increase motivation for regular physical exercise and help improve the health of students.
Keywords: physical education; motivation; physical education program